Pembelajaran Bahasa Arab Materi Muhadatsah dengan Metode Audiolingual pada Santriwati Kelas 1 E Madrasah Tsanawiyah Islam Al Mukmin Ngruki Sukoharjo Tahun Ajaran 2022/2023 - Rizkha Khafidhotul Iskarimah (Sekolah Tinggi Islam Al-Mukmin (STIM) Surakarta, 2022)
This research is motivated by the strategy used in the process of teaching muhadatsah (Arabic conversation) at MTs Islam Al Mukmin. In Arabic language learning, the female students are presented with the mubasyaroh method, in which only the teacher is required to be active, while the students tend to be passive during the teaching and learning process. Another factor is the varying abilities of the students—some already have prior knowledge of Arabic, while others have no familiarity with the language at all. Therefore, it is necessary to use varied strategies or methods in the Arabic language learning process. This research is a Classroom Action Research using a qualitative approach. The subjects of the study are 25 female students from class 1E at MTs Islam Al Mukmin Ngruki. Based on the results, it can be concluded that the use of the Sam’iyyah Syafahiyyah method is effective in improving the students’ muhadatsah skills and is particularly suitable for beginners, especially the students of class 1E at MTs Islam Al Mukmin Ngruki.